2012
DOI: 10.1002/wnan.1184
|View full text |Cite
|
Sign up to set email alerts
|

DNA‐based plasmonic nanoarchitectures: from structural design to emerging applications

Abstract: Plasmonic nanoarchitectures refer to the well-defined groupings of elementary metallic nanoparticle building blocks. Such nanostructures have a plethora of technical applications in diagnostics, energy-harvesting, and nanophotonic circuits, to name a few. Nevertheless, it remains challenging to construct plasmonic nanoarchitectures at will inexpensively. Bottom-up self-assembly is promising to overcome these limitations, but such methods often produce defects and low-yields. For these purposes, DNA has emerged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 108 publications
(113 reference statements)
0
21
0
Order By: Relevance
“…Among all inorganic nanoparticles, noble metal nanoparticles especially gold and silver are of special research interest owing to their strong LSPR effect. Plasmonic nanoarchitectures have been constructed by bottomup self-assembly and/or top-down lithography, showing a number of applications in diagnostics, energy-harvesting, nanophotonic circuits and so on [28]. Recent studies including our group's results have found that when chiral molecules or their assemblies are in proximity to noble metal nanoparticles, plasmon-induced CD in the visible or near-infrared region will appear owing to transportation of chirality from chiral molecules or templates to nanoparticles [29][30][31].…”
Section: Resultsmentioning
confidence: 99%
“…Among all inorganic nanoparticles, noble metal nanoparticles especially gold and silver are of special research interest owing to their strong LSPR effect. Plasmonic nanoarchitectures have been constructed by bottomup self-assembly and/or top-down lithography, showing a number of applications in diagnostics, energy-harvesting, nanophotonic circuits and so on [28]. Recent studies including our group's results have found that when chiral molecules or their assemblies are in proximity to noble metal nanoparticles, plasmon-induced CD in the visible or near-infrared region will appear owing to transportation of chirality from chiral molecules or templates to nanoparticles [29][30][31].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the tunable surface modification of AuNP gives rise to a myriad of biosensor prototypes. [79][80][81] To this end, a sandwich-like structure made of DNA-AuNP-Raman Tag (RTag) probes was fabricated to capture alternative splice variants. [82][83][84][85] The intrinsic sharp Raman peaks (a full width at halfmaximum of 1 nm in comparison to that of 50 nm for the FITC fluorescence) 86 and the enhancement factor of SERS (10 10 to 10 11 ) 87 enable multilabel readouts at a single-wavelength excitation.…”
Section: Raman Methodsmentioning
confidence: 99%
“…The strong LSPR of AuNP makes it a potent substrate for Raman enhancement. In addition, the tunable surface modification of AuNP gives rise to a myriad of biosensor prototypes . To this end, a sandwich‐like structure made of DNA‐AuNP‐Raman Tag (RTag) probes was fabricated to capture alternative splice variants .…”
Section: Biological Significance Of Alternative Splicingmentioning
confidence: 99%
“…237,238 One- , 239 two- 240 and three-dimensional 241 structures can be made, and the ability of other nanoscale objects to be functionalized with DNA, combined with the specificity conferred by complementary sequence recognition 242,243 means that DNA can connect and organize disparate nanostructures to make relatively complex constructs, 244,245, 246,247,248,249,250,251,252 including well-controlled nanoparticle crystal lattices, 253,254255,256,257,258 and even active systems. 259,260,261,262,263 DNA origami 264 is a prime example of the power of DNA to control the arrangement of nanoscale objects, providing a molecularly precise “breadboard” to which nanostructures can be attached.…”
Section: Dna-based Self-assemblymentioning
confidence: 99%